2023
DOI: 10.1037/pha0000614
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis craving in response to alcohol cues among adolescents and young adults in the laboratory and in daily life.

Abstract: Cannabis use among adolescents and young adults who drink alcohol is prevalent and relates to poorer clinical outcomes. Interrelated factors, such as cross-reactivity to alcohol cues, may contribute to the high prevalence of cannabis use among young persons who drink alcohol. We tested whether systematic presentation of alcohol cues in the laboratory and naturalistic presence of alcohol cues in daily life elicit cannabis craving. Data were compiled from two clinical trials. Participants (N = 54) were adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
3
13
2
Order By: Relevance
“…The consistency of daily life results between this study and our previous sample (Wycoff et al, 2023) is notable for a few reasons.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…The consistency of daily life results between this study and our previous sample (Wycoff et al, 2023) is notable for a few reasons.…”
Section: Discussionsupporting
confidence: 80%
“…We examined whether alcohol cues are associated with elevated predicted elevated cannabis craving among adolescents and emerging adults, though we did not find the parallel association in the laboratory (Wycoff et al, 2023). In this study, we sought to examine similar questions with a younger sample of adolescents who had not yet progressed to moderate or severe AUD and to examine alternative control conditions for alcohol cues in the laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One other study, to our knowledge, has bridged the human laboratory and natural environment with youth. Wycoff et al (2022) examined in vivo cue reactivity in the lab and natural environment and found alcohol‐induced cannabis craving in the laboratory predicted greater daily cannabis craving in the natural environment.…”
Section: Introductionmentioning
confidence: 99%